The role of autonomy support and integration in predicting and changing behaviour: theoretical and practical perspectives on self-determination theory - McLachlan, Sarah (2011)
This thesis reports six studies adopting a self-determination theory (SDT; Deci & Ryan, 1985) approach to understanding motivation and behaviour in health and social contexts. The research focuses on the internalisation and integration of goals and motives extrinsic to the individual and the effects of internalisation on psychological and behavioural outcomes. Two studies also explore the role of social agents in facilitating internalisation through provision of autonomy support.